The union of narrative and executive function: different but complementary - Friend, Margaret; Bates, Raven Phoenix (Frontiers in Psychology, 2014)
Oral narrative production develops dramatically from 3 to 5 years of age, and is a key factor in a child’s ability to communicate about the world. Concomitant with this are developments in executive function (EF). For example, executive attention and behavioral inhibition show marked development beginning around 4 years of age. Both EF and oral narrative abilities have important implications for academic success, but the relationship between them is not well understood. The present paper utilizes a cross-lagged design to assess convergent and predictive relations between EF and narrative ability. As a collateral measure, we collected a Language Sample during 10 minutes of free play. Language Sample did not share significant variance with Narrative Production, thus general language growth from Wave 1 to Wave 2 cannot account for the predictive relations between EF and Narrative. Our findings suggest that although EF and Narrative ability appear independent at each wave, they nevertheless support each other over developmental time. Specifically, the ability to maintain focus at 4 years supports subsequent narrative ability and narrative ability at 4 years supports subsequent facility and speed in learning and implementing new rules.